The Evolution of Ecological Diversity in Acidobacteria - Sikorski, Johannes; Baumgartner, Vanessa; Birkhofer, Klaus; Boeddinghaus, Runa S.; Bunk, Boyke; Fischer, Markus; Fösel, Bärbel U.; Friedrich, Michael W.; Göker, Markus; Hölzel, Norbert; Huang, Sixing; Huber, Katharina J.; et al. (Frontiers in Microbiology, 2022)
Acidobacteria occur in a large variety of ecosystems worldwide and are particularly abundant and highly diverse in soils. In spite of their diversity, only few species have been characterized to date which makes Acidobacteria one of the most poorly understood phyla among the domain Bacteria. We used a culture-independent niche modeling approach to elucidate ecological adaptations and their evolution for 4154 operational taxonomic units of Acidobacteria. Using the relative abundances of 16S rRNA gene transcripts, niche optima were modeled for active OTUs along the gradients of 41 environmental variables determined across 150 different comprehensively characterized grassland soils in Germany. By linking 16S rRNA transcripts to the phylogeny of full 16S rRNA gene sequences, we could trace the evolution of the different ecological adaptations during the diversification of Acidobacteria. This approach revealed a pronounced ecological diversification even among acidobacterial sister clades. Although the evolution of habitat adaptation was mainly cladogenic, it was disrupted by recurrent events of convergent evolution that resulted in frequent habitat switching within individual clades. Our findings indicate that the high diversity of soil acidobacterial communities is largely sustained by differential habitat adaptation even at the level of closely related species. A comparison of niche optima of individual OTUs with the phenotypic properties of their cultivated representatives showed that our niche modeling approach provides information on ecological adaptations that cannot be inferred from standard taxonomic descriptions of bacterial isolates. This novel information can guide the cultivation of not-yet-cultivated species in the future.